On static spherically symmetric solutions of Einstein's equations with two perfect fluids as source - Uzun, Nebiye Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
We first point out that in the context of static spherically symmetric solutions of Einstein's Equations, the "radially imperfect fluids" introduced recently are equivalent to superpositions of noninteracting normal and tachyonic perfect fluid sources, also discussed recently. We discuss the given solutions, challenging especially the black hole interpretations, and give more examples of this type. We then ask what we can find about solutions with two noninteracting perfect fluids as source, where more than one component of the fluid four-velocities is nonzero, unlike in the single-fluid case. We find that such solutions exist; that is, even in a static spacetime, the source fluids can be moving, if there is more than one.
Keywords: Einstein field equations.